Use of Nanomaterials in Cryobiology and Cryomedicine - Goltsev, Anatoliy; Bondarovych, Mykola; Babenko, Natalya; Gaevska, Yuliya; Dubrava, Tatiana; Ostankov, Maksim (Problems of Cryobiology and Cryomedicine, 2020)
The review considers the possibility of using modern nanotechnological developments aimed to achieve alternative cryobiological goals. On the one hand, the use of nanomaterials will increase the functional value of thawed cells due to such unique characteristics of nanoparticles as size, shape, surface charge, chemical composition, etc. Nanomaterials can be used as nanocontainers for impermeable cryoprotective agents (CPAs) and cause signiﬁcant changes in crystal formation, thermal conductivity and other properties of cells, tissues and organs, that increases the eﬃciency of their cryopreservation. On the other hand, the combined use of nanomaterials and low-temperature freezing factors is considered a promising method of destruction of pathologically altered cells and tissues, as it minimizes the risk of recurrence of oncopathology after insuﬃcient freezing-out of the tumor site. Probl Cryobiol Cryomed 2020; 30(4): 313–330